2022
DOI: 10.3390/polym14245515
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of 3D-Printed Polymer Lattices with Varied Design and Processing Strategies

Abstract: Emerging polymer 3D-printing technologies are enabling the design and fabrication of mechanically efficient lattice structures with intricate microscale structures. During fabrication, manufacturing inconsistencies can affect mechanical efficiency, thereby driving a need to investigate how design and processing strategies influence outcomes. Here, mechanical testing is conducted for 3D-printed lattice structures while altering topology, relative density, and exposure time per layer using digital light processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The effects of design and processing strategies have been studied for lattices fabricated with DLP printing. Microscopy measurements have determined that structures with higher relative density and more beams per unit cell tended to print with more material than expected compared to other designs [7]. Mechanical testing demonstrated that the added material improved mechanical properties.…”
Section: Validationmentioning
confidence: 98%
See 1 more Smart Citation
“…The effects of design and processing strategies have been studied for lattices fabricated with DLP printing. Microscopy measurements have determined that structures with higher relative density and more beams per unit cell tended to print with more material than expected compared to other designs [7]. Mechanical testing demonstrated that the added material improved mechanical properties.…”
Section: Validationmentioning
confidence: 98%
“…Design for additive manufacturing (DfAM) provides a framework that facilitates decision making with AM technologies. DfAM is a multifaceted field of study in which diverse topics such as creativity [3], bioinspiration [4], materials [5], optimization [6], and validation [7] are all considered for enhancing AM design with integrated approaches. Advances in DfAM are necessary to keep up with the exponential increase in interest for AM applications [8], especially in fields such as medicine that benefit from on-demand design and manufacturing for personalized solutions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Composites of thermoset resins reinforced with continuous fiber are commonly used in high-performance composite applications, including aerospace, high-performance automobiles, boats, various sporting goods, medical, and wind turbines for renewable energy [ 12 , 13 , 14 , 15 , 16 ]. These are used in favor over thermoplastic composites for these high-performance applications because their lower initial viscosity allows for much higher fiber reinforcement content resulting in improved strength and stiffness and much higher resistance to creep.…”
Section: Introductionmentioning
confidence: 99%